2021
DOI: 10.1186/s12870-021-02918-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of cucumber seedlings to low temperature stress by reducing nitrate to ammonium during it’s transportation

Abstract: Background Low temperature severely depresses the uptake, translocation from the root to the shoot, and metabolism of nitrate and ammonium in thermophilic plants such as cucumber (Cucumis sativus). Plant growth is inhibited accordingly. However, the availability of information on the effects of low temperature on nitrogen transport remains limited. Results Using non-invasive micro-test technology, the net nitrate (NO3−) and ammonium (NH4+) fluxes i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…An appropriate ratio of NH 4 + : NO 3 -(10:90) has effectively mitigated the low light intensity stress in Brassica pekinensis by modulating the expression of ammonium assimilatory enzymes, such as GS and NR [105]. In cucumber, the greater flux rate of NH 4 + into vascular bundles of the lateral vein, midrib, and shoot tip, due to the increased conversion of NO 3 to NH 4 + , has substantially aided in overcoming low-temperature stress, as an energy conservatory mechanism [130]. An equal ratio of ammonium and nitrate (50:50) was found to improve the biomass, photosynthetic efficiency, protein content, and decrease lipid peroxidation in baby lettuce under heat stress conditions [131].…”
Section: Ameliorated Crop Resilience To Biotic and Abiotic Stresses B...mentioning
confidence: 99%
“…An appropriate ratio of NH 4 + : NO 3 -(10:90) has effectively mitigated the low light intensity stress in Brassica pekinensis by modulating the expression of ammonium assimilatory enzymes, such as GS and NR [105]. In cucumber, the greater flux rate of NH 4 + into vascular bundles of the lateral vein, midrib, and shoot tip, due to the increased conversion of NO 3 to NH 4 + , has substantially aided in overcoming low-temperature stress, as an energy conservatory mechanism [130]. An equal ratio of ammonium and nitrate (50:50) was found to improve the biomass, photosynthetic efficiency, protein content, and decrease lipid peroxidation in baby lettuce under heat stress conditions [131].…”
Section: Ameliorated Crop Resilience To Biotic and Abiotic Stresses B...mentioning
confidence: 99%
“…Two homologous genes in cucumber, CsNPF6.2 and CsNPF6.3 , are highly expressed in the petioles of young leaves and may be responsible for the storage of nitrate in the petioles of young leaves. Liu et al showed that low temperature treatment significantly inhibited the expression of CsNPF6.3 ( CsNRT1.4a ) in petiole and midrib, which may be closely related to nitrate transport in petiole and midrib, which further verified the function of CsNPF6.3 in petiole [ 55 ]. In addition, CsNPF6.2 was significantly expressed in cucumber tendrils, indicating that it may differentiate into other functions, in addition to mediating nitrate storage.…”
Section: Discussionmentioning
confidence: 95%
“…N is the most essential mineral nutrient for plants [ 48 ] and plays a critical role in the synthesis of amino acids, proteins, and nucleic acids [ 49 ]. Plant roots primarily take up nitrogen in the form of nitrate anions (NO 3 − ) and ammonium cations (NH 4 + ), with terrestrial plants favouring NO 3 − [ 50 ].…”
Section: Resultsmentioning
confidence: 99%